Feasibility of filtering crude palm oil slurry - Abdul Aziz, Ramlan; Saidi, Hamdani; Ripin, Adnan; Mohamed, Nor H. (1991)
This paper presents the results of an initial investigation on the viability of filtration in replacing the current clarification process in crude palm oil slurry separation. Initial investigation were done using laboratory size filter press to determine the CPO filtration characteristics and the suitable filter media.